A CONTENT ANALYSIS OF THE WRITING ACTIVITIES IN ACTION PACK 10 TO MEASURE THE DEGREE OF THEIR CONGRUENCE WITH THE GENERAL GRADE OUTCOMES FOR THE ENGLISH LANGUAGE GUIDELINES IN JORDAN - Al-Qadi, Haitham M.; Al-Qadi, Kifah R. (European Scientific Journal, ESJ, 2015)
The present study aimed at analyzing the writing activities in Action Pack 10 and measuring the degree of their congruence with the general grade outcomes for the English language guidelines in Jordan. The material of the analysis is the English language textbook for the 10th grade within Action Pack series. The researchers content-analyzed the writing activities in all the units in both parts of the book; they compared the content of these activities with the main five general outcomes for the guidelines of teaching writing in this grade. The results of the study showed that the second and the third outcomes, as listed in the third and fourth sections of the paper, ranked first with a percentage of 24.5%; second ranked the fourth and fifth outcomes with a percentage of 18.3% ; and finally, the first outcome ranked third with a percentage of 14.3%. The researchers presented some inferences that are related to the results of the analysis.